Quality of soursop juice after pectinase enzyme treatment - Yusof, Saimah; lbrahim, Nurzarina (Elsevier, 1994)
A pectinase enzyme was used at 0-0.1% concentrations to help in the extraction of soursop juice. The incubation times were from 1–3 h. The juices obtained were evaluated for yield, titratable acidity, pH, ascorbic acid, total soluble solids, viscosity, turbidity and sugar contents. Results indicated that the use of enzyme was beneficial as it increased the yield of juice by 41%. There were significant increases in acidity and Brix and significant decreases in viscosity and turbidity. There were no significant changes in the ascorbic acid and sugar contents. Sensory evaluation results indicate that the extracted juice was superior in quality to a commercial product.